Kedudukan Electronic Documents Sebagai Alat Bukti Dalam Sengketa Kepabeanan Di Pengadilan Pajak - Azmi Fahri (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
The Tax Court is a judicial body that exercises jurisdiction over Taxpayers or Tax insurers seeking justice in tax disputes, including customs disputes. Customs disputes are discrepancies in opinion or interpretation of statutory provisions, calculation, and determination of the amount of import duty, excise, and Import Tax that should be paid between Customs service users and the Directorate General of Customs and Excise. Along with the rapid progress of science and technology, the world is now entering the digital era. Thus, there is strong pressure on the law, including the law of evidence, to harmonize and follow developments in society. The research was conducted with a normative juridical approach, with the conclusion that in seeking material truth to resolve Customs disputes in the Tax Court, the Judge may request evidence from the Appellant in which all information regarding the import and export process is available on the application system of the Directorate General of Customs and Excise. Thus, all available electronic information can be printed and used as evidence in the Tax Court. In addition, the Tax Court adheres to the principle of free evidence, where the evidence can be in the form of letters or documents, expert statements, witness statements, confessions of the parties, and/or the knowledge of the judge.